Flexible, Water-Resistant and Air-Stable LiBH4 Nanoparticles Loaded Melamine Foam With Improved Dehydrogenation - Fan, Yanping; Chen, Dandan; Yuan, Zhenluo; Chen, Qiang; Fan, Guangxin; Zhao, Dan; Liu, Baozhong (Frontiers in Chemistry, 2020)
Flexible, water-resistant and air-stable hydrogen storage material (named PMMA-LiBH4/GMF), consisting of LiBH4 nanoparticles confined by poly (methylmethacrylate) (PMMA) and reduced graphene oxide (rGO) modified melamine foam (GMF), were prepared by a facile method. PMMA-LiBH4/GMF can recover original shape after compression at the strain of 50 % and exhibits highly hydrophobic property (water contact angle of 123 °). Owing to the highly hydrophobic property and protection of PMMA, PMMA-LiBH4/GMF demonstrates outstanding water-resistance and air-stability. Significantly, the onset dehydrogenation temperature of PMMA-LiBH4/GMF at first step is reduced to 94 °C, which is 149 °C less than that of LiBH4/GMF, and the PMMA-LiBH4/GMF desorbs 2.9 wt% hydrogen within 25 min at 250 °C, which is obviously more than the dehydrogenation amount of LiBH4/GMF under the same conditions. It’s our belief that the flexible, water-resistant and air-stable PMMA-LiBH4/GMF with a simple preparation route will provide a new avenue to the research of hydrogen storage materials.